2018
DOI: 10.1136/oemed-2017-104976
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer risk and occupational exposures in crop farming: results from the AGRIculture and CANcer (AGRICAN) cohort

Abstract: Our results suggest associations between lung cancer and several crop-related tasks, even if we cannot rule out some chance findings due to multiple comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…The odds ratio in our study was slightly higher than in the Baser study but comparable with a cohort study by Alavanja et al [30]. Many other studies have proved that pesticides are associated with an increased risk of lung cancer in agriculture workers [30][31][32][33][34]. [3].…”
Section: Discussionsupporting
confidence: 86%
“…The odds ratio in our study was slightly higher than in the Baser study but comparable with a cohort study by Alavanja et al [30]. Many other studies have proved that pesticides are associated with an increased risk of lung cancer in agriculture workers [30][31][32][33][34]. [3].…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were replicated in later studies with the AHS cohort [ 10 ]. The AGRIculture and CANcer (AGRICAN) cohort study of French farmers also suggested associations between the risk of small-cell lung cancer and exposure to pesticides (HR, 2.38; 95% CI, 1.07 to 5.28) [ 11 ]. These significant trends in the risk of lung cancer were also observed in our adjusted results.…”
Section: Discussionmentioning
confidence: 99%
“…Increased lung cancer-related mortality among pesticide applicators has been reported [4][5][6][7][8], suggesting the possibility that exposure to pesticides may increase the risk of lung cancer among farmers [9]. In addition, previous cohort studies reported positive associations between exposure to pesticides and the occurrence of lung cancer [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Europe, India, and Brazil are also major users of agricultural pesticides, which represent a potential problem for non-target organisms, including humans (Hossard et al 2017 ; Paumgartten 2020 ; Zheng et al 2020 ). In France, the AGRICAN (Agriculture and Cancer) cohort study, which began in 2005, has provided important insight into rare diseases due to the large number of participants—more than 181,000 individuals (Tual et al 2013 ; Lemarchand et al 2016 ; Piel et al 2017 , 2019 ; Boulanger et al 2018 ). One study in France showed that more than half (54.4%) of the 408 cases of occupational exposure to pesticides referred to a poison control center between 2012 and 2016 involved insecticides, while a third (33.3%) involved herbicides, and 12.2%, fungicides (Boucaud-Maitre et al 2019 ; Tual et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%